(3EUOGQ GdMce GdbVGFj Ydi VhA Gdabg hCMcGe GdbVGA (B:s (3OQGSI JMdjdjI hJWHjbjI (B/s - (3GdJMjhj, eMehO GdSjO YeQs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2011)
(3jJfGhd cJGH (B((3EUOGQ GdMce GdbVGFj Ydi VhA Gdabg hCMcGe GdbVGA (B: "(3OQGSI JMdjdjI hJWHjbjI(B") (3hGdPj bGe HJCdjag O(B. (3eMehO GdSjO YeQ GdJMjhj aj MhGdj (B(447) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdMce GdbVGFj(B)(3, jSJYQV GdcJGH SHYI ehVhYGJ NGUI HYO eQGMd SjQ fXQ GdbVjI MJi EUOGQ GdMce GdbVGFj, hgj (B: (3GdChd (B: (3GdeOGhdI GdbVGFjI, GdKGfj (B: (3GdfWb HGdMce, GdKGdK (B: (3cJGHI GdMce GdbVGFj, GdQGHY (B: (3eVehf GdMce GdbVGFj, GdNGeS (B: (3JSHjH GdMce GdbVGFj, GdSGOS (B: (3eUGQja GdNUheI GdbVGFjI, GdSGHY (B: (3EUOGQ Mce GdJMcje(B. s
(3HHdjhLQGajI (B: (3UaMI (B411-440.s
Keywords: (3GdCMcGe (B((3bGfhf eQGaYGJ(B)s -- (3eUQs; (3GdCMcGe GdTQYjIs